Surgical Management of Compound Odontoma Associated with Unerupted Tooth - Andrea Pacifici; Daniele Carbone; Roberta Marini; Luciano Pacifici (Case Reports in Dentistry)
Odontomas represent the most common type of odontogenic benign jaws tumors among patients younger than 20 years of age. These tumors are composed of enamel, dentine, cementum, and pulp tissue. According to the World Health Organization classification, two distinct types of odontomas are acknowledged: complex and compound odontoma. In complex odontomas, all dental tissues are formed, but appeared without an organized structure. In compound odontomas, all dental tissues are arranged in numerous tooth-like structures known as denticles. Compound odontomas are often associated with impacted adjacent permanent teeth and their surgical removal represents the best therapeutic option. A case of a 20-year-old male patient with a compound odontoma-associated of impacted maxillary canine is presented. A minimally invasive surgical technique is adopted to remove the least amount of bone tissue as far as possible.